Tree-Indexed Random Walks On Groups And First Passage Percolation - Benjamini, Itai; Peres, Yuval (Probability Theory and Related Fields, 1994)
Suppose that i.i.d. random variables are attached to the edges of an infinite tree. When the tree is large enough, the partial sumsSσ along some of its infinite paths will exhibit behavior atypical for an ordinary random walk. This principle has appeared in works on branching random walks, first-passage percolation, and RWRE on trees. We establish further quantitative versions of this principle, which are applicable in these settings. In particular, different notions of speed for such a tree-indexed walk correspond to different dimension notions for trees. Finally, if the labeling variables take values in a group, then properties of the group (e.g., polynomial growth or a nontrivial Poisson boundary) are reflected in the sample-path behavior of the resulting tree-indexed walk.